Tantangan Implementasi Kompetensi Profesional dalam PAK Berbasis AI : Upaya Mempersiapkan Generasi Emas di SD Negeri 071162 Esiwa - Asliwati Zebua; Damayanti Nababan (Damai : Jurnal Pendidikan Agama Kristen dan Filsafat, 2025)
This study aims to identify challenges and formulate strategies for the implementation of professional competencies of Christian Religious Education (PAK) teachers based on artificial intelligence (AI) at the primary school level, with a focus on SD Negeri 071162 Esiwa. The background of this study begins with the increasing demands of the digital curriculum, while PAK teachers still face limitations in technological literacy, digital infrastructure, and the availability of contextualized Christian faith-based learning media. This study used a descriptive qualitative approach with data collection techniques through interviews, classroom observations, and documentation. The research subjects consisted of one principal and ten students in grades IV-VI. The results showed that low mastery of technology by teachers, limited digital devices, and lack of institutional support are the main obstacles in the integration of AI in PAK learning. However, AI has great potential to enhance students' learning experience spiritually and digitally through interactive, visual, and narrative Bible-based approaches. This research recommends spiritual technology-based teacher training, strengthening school infrastructure, developing contextualized teaching materials based on local culture, and collaboration between schools, churches, and Christian app developers. The findings contribute to the development of an adaptive, contextual, and transpersonal PAK learning model.